Islamic Ethical Guidance in the Digital Age: A Study of MUI Fatwas on Social Media Use in Indonesia - Rahman, Abdul; Mulsir Irawanda; Syukri (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2024)
This study aims to examine the Indonesian Ulema Council (MUI)’s fatwas concerning the use of social media, focusing on their ethical foundations, influence on user behavior, and the challenges encountered in their societal implementation. The research seeks to assess how Islamic legal norms are applied to contemporary digital practices and to what extent these fatwas shape public engagement in online platforms. Employing a qualitative content analysis method, the study reviews selected MUI fatwas issued between 2017 and 2023. In addition, semi-structured interviews were conducted with Islamic legal scholars and active social media users to gain insight into public understanding and response to these fatwas. Data were analyzed through thematic coding, supported by relevant Islamic legal theory. The findings indicate that MUI fatwas recognize social media as a neutral tool (mubāḥ) whose moral value depends on its usage. The fatwas emphasize ethical conduct, the avoidance of harmful content, and the promotion of beneficial communication. While the fatwas provide normative guidance aligned with Islamic principles, their practical enforcement is limited by users' digital habits, lack of awareness, and insufficient public dissemination. This study contributes to the growing field of digital Islamic ethics by offering an in-depth look at how formal religious authorities engage with technological challenges. It highlights the need for more effective strategies in communicating religious norms to digitally active Muslim communities, suggesting collaboration between religious institutions, digital influencers, and educational platforms to enhance the social impact of fatwas in the online sphere.